ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL KEMAMPUAN KONEKSI MATEMATIS SISWA MTs - Pamila Malinda; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze students errors in solving the problems of students mathematical connection ability and the extent to which students make these mistakes and to determine the level of connection ability that students have. The method used in this study is descriptive method with a qualitative approach. The samples in this study were as many as 22 students in one MTs in Cimahi City, the results obtained were that the lowest percentage was obtained in the indicator identifying the relationship of one procedure to another procedure in an equivalent representation of 67.04%. Then the error made by the students are not thorough in understanding the questions given and not identifying the known elements and concepts that are contained so that the completion process given is not appropriate other than that the calculation process is done incorrectly, especially those that include calculating the algebraic form.